The impact of User-Characteristics and Organizational-Characteristics on End-user Satisfaction with Enterprise Resource Planning (ERP) systems - Seneviratne, S M Chaturika; Colombage, Lashini (International Journal of Financial, Accounting, and Management, 2023)
Purpose: This study aims to examine characteristics that influence end-user satisfaction with ERP systems within the Sri Lankan context to understand what critical factors should be considered in the ERP decision-making processes. Research methodology: Data collection is conducted through an online questionnaire targeting end-users of ERP systems belonging to various industries. Results: The study found a significant relationship between five user characteristics and end-user satisfaction, as well as the significance of usability to end-user satisfaction. Minimal memory load was found to have no significant relationship with end-user satisfaction. In terms of organisational characteristics, user training and top-management support had a significant influence on end-user satisfaction as well. Limitations: Since this study is on ERP systems such as SAP, IFS, and Oracle with a high industry focus, organisations that do not use commercial ERP systems are not considered particularly public-sector organizations. Contributions: Although previous studies emphasised various factors that contributed to implementation failures, those factors have not been given importance to end-user satisfaction or the success of an ERP system. Within the Sri Lankan context, ERP implementations are still in the early stages, so it would be very useful to understand the factors that affect user satisfaction with such systems. Novelty: The findings identify what factors ERP vendors can focus on when making changes to their commercial products and give managers an idea of what factors they should consider when choosing the right ERP system for an organization.